2020
DOI: 10.1136/neurintsurg-2019-015499
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of intracranial pressure quantifies vasodilatory effect of verapamil to treat cerebral vasospasm

Abstract: IntroductionAfter aneurysmal subarachnoid hemorrhage (SAH), both proximal and distal cerebral vasospasm can contribute to the development of delayed cerebral ischemia. Intra-arterial (IA) vasodilators are a mainstay of treatment for distal arterial vasospasm, but no methods of assessing the efficacy of interventions in real time have been established.ObjectiveTo introduce a new method for continuous intraprocedural assessment of endovascular treatment for cerebral vasospasm.MethodsThe premise of our approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…The use of IA vasodilators is a relatively safe treatment, with immediate improvement in cerebral perfusion. Recent studies have demonstrated the immediate impact on cerebral perfusion after infusion of verapamil with a dose-dependent response 14. Unfortunately, the effect of these medications is temporary and in many cases they fail to achieve adequate vessel dilation, with frequent recurrence of CV requiring multiple treatments 15 16.…”
Section: Discussionmentioning
confidence: 99%
“…The use of IA vasodilators is a relatively safe treatment, with immediate improvement in cerebral perfusion. Recent studies have demonstrated the immediate impact on cerebral perfusion after infusion of verapamil with a dose-dependent response 14. Unfortunately, the effect of these medications is temporary and in many cases they fail to achieve adequate vessel dilation, with frequent recurrence of CV requiring multiple treatments 15 16.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is probably the most difficult to defining therapeutics. Although initial medical management of IH and cerebral tissue hypoxia is based on individual institutional guidelines or international consensus [ 4 , 66 , 67 ], it is essential to keep in mind the following premises: (a) close, continued follow-up monitoring and further therapeutic response based on wave morphology [ 68 , 69 ]; (b) refrain from escalation of any medical treatment beyond recommended levels, if the response to that intervention is not satisfactory; and (c) early consideration of CSF drainage and/or surgical evacuation of space-occupying injuries or decompression of the cranial cavity.…”
Section: Therapeutical Approachmentioning
confidence: 99%
“…Associations with other parameters and diagnoses were described as well (Hamilton et al 2016, Kasprowicz et al 2012. The method was also used to characterize cerebral vascular changes during acute ICP drop in subarachnoid hemorrhage (Liu et al 2019, Liu et al 2020. However, it has not found widespread entry into clinical routine so far.…”
Section: Introductionmentioning
confidence: 99%